Hubungan Pengetahuan dan Dukungan Sosial dengan Kecemasan Perawat dalam Merawat Pasien COVID-19 - Dian Wiko; Mahyar Suara; Farida Murtiani (Jurnal Kesehatan Saelmakers PERDANA, 2023)
COVID-19 pandemic has become a major threat to public health, especially nurses. Nurses as the front line are vulnerable to psychological disorders such as anxiety. The purpose of this study was to determine the relationship between knowledge and social support with nurse anxiety in treating COVID-19 patients at RSPI Prof. Dr. Sulianti Saroso. Quantitative research with cross sectional design. Sample of nurses caring for COVID-19 patients. A sample of 136 nurses was taken by purposive sampling technique. Collecting data using a questionnaire using a google form. Univariate analysis using frequency distribution, bivariate analysis using chi square. The results showed that of the 136 nurses who treated COVID-19 patients, half of them were in the non-anxious category, namely 81 (59.6%)%, 50 (36.8%) mild anxiety, namely 50 (36.8%) and 5(3, 7%) moderate anxiety. Most of them had good knowledge about COVID-19, namely 101 (74.3%) and stated that social support was in the supportive category, namely 71 (52.1%). There is a relationship between social support and the anxiety level of the COVID-19 screening nurse (p value = 0.004). There is a relationship between social support and nurses' anxiety level (p value = 0.000).